The Psychological Gains from COVID-19 Vaccination: Who Benefits the Most? - Manuel Bagues; Velichka Dimitrova (Institute of Labor Economics (IZA), 2021)
We quantify the impact of COVID-19 vaccination on psychological well-being using information from a large-scale panel survey representative of the UK population. Exploiting exogenous variation in the timing of vaccinations, we find that vaccination increases psychological well-being by 0.12 standard deviation, compensating for around one half of the overall decrease caused by the pandemic. This effect persists for at least two months, and it is associated with a decrease in the perceived likelihood of contracting COVID-19 and higher engagement in social activities. The improvement is 1.5 times larger for mentally distressed individuals, supporting the prioritization of this group in vaccination roll-outs.
Keywords: I18; I31; 330; psychological well-being; COVID-19; vaccination